Bacillus subtilis Nucleoid-Associated Protein YlxR Is Involved in Bimodal Expression of the Fructoselysine Utilization Operon (frlBONMD-yurJ) Promoter - Ogura, Mitsuo; Shindo, Kazutoshi; Kanesaki, Yu (Frontiers in Microbiology, 2020)
Bacteria must survive harsh environmental fluctuations at times and have evolved several strategies. “Collective” behaviors have been identified due to recent progress in single-cell analysis. Since most bacteria exist as single cells, bacterial populations are often considered clonal. However, accumulated evidence suggests this is not the case. Gene and protein expression is often not homogeneous, resulting in phenotypic heterogeneity. In extreme cases, this leads to bistability, the existence of two stable states. In many cases, expression of key master regulators is bimodal via positive feedback loops causing bimodal expression of the target genes. We observed bimodal expression of metabolic genes for alternative carbon sources. Expression profiles of the frlBONMD-yurJ operon driven by the frlB promoter (PfrlB), which encodes degradation enzymes and a transporter for amino sugars including fructoselysine, were investigated using transcriptional lacZ and gfp, and translational fluorescence reporter mCherry fusions. Disruption effects of genes encoding CodY, FrlR, RNaseY, and nucleoid-associated protein YlxR, four known regulatory factors for PfrlB, were examined for expression of each fusion construct. Expression of PfrlB-gfp and PfrlB-mCherry, which were located at amyE and its original locus, respectively, was bimodal and disruption of ylxR resulted in disappearance of the clear bimodal expression pattern in flow cytometric analyses. This suggested a role for YlxR on the bimodal expression of PfrlB. The data indicated YlxR acted on the bimodal expression of PfrlB through both transcription and translation. YlxR regulates many genes, including those related to translation, supporting above notion. Depletion of RNaseY abolished heterologous expression of transcriptional PfrlB-gfp but not bimodal expression of translational PfrlB-mCherry, suggesting the role of RNaseY in regulation of the operon through mRNA stability control and control for PfrlB-mCherry at the translational level. Based on these results, we discuss the meaning and possible cause of bimodal PfrlB expression.